2022
DOI: 10.3390/cancers14246124
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Circulating Levels of Advanced Glycation End-Products and Their Soluble Receptor (AGEs-RAGE Axis) with Risk and Mortality of Breast Cancer

Abstract: The interaction of advanced glycation end-products (AGEs) with their receptor (RAGE) elicits oxidative stress and inflammation, which is involved in the development of breast cancer. However, large-scale population-based evidence exploring genetically modified circulating levels of AGEs-RAGE axis with risk and mortality of breast cancer is scarce. We recruited 1051 pairs of age-matched breast cancers and controls and measured plasma AGEs and sRAGE concentrations by enzyme-linked immunosorbent assay (ELISA). Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Higher levels of AGEs and the AGEs/RAGE ratio were associated with an increased risk of breast cancer. The authors also documented a positive association between AGEs and poor prognosis [69].…”
Section: Posttranslational Protein Modifications-agesmentioning
confidence: 86%
“…Higher levels of AGEs and the AGEs/RAGE ratio were associated with an increased risk of breast cancer. The authors also documented a positive association between AGEs and poor prognosis [69].…”
Section: Posttranslational Protein Modifications-agesmentioning
confidence: 86%
“…The study population consisted of 107 paired breast cancer patients and controls, simply randomly extracted from a hospital-based case–control study we set up [ 26 ]. As described in our previous study [ 27 ], the cases were patients with newly diagnosed and histologically confirmed breast cancer from Tianjin Medical University Cancer Institute and Hospital since 1 January 2003. They had no history of other malignancies, no reception of any treatment before admission, and no history of blood transfusion in the last 6 months prior to blood sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Oral vitamin D3 (50,000 IU), administered once every 8 weeks, was found to augment sRAGE levels in women with PCOS, as reported in a recent phase IV clinical trial conducted by Maimonides Medical Center, USA [ 130 ]. Now this result is highly crucial with respect to the fact that reduced sRAGE levels and high plasma AGEs have been reported in patients with breast cancer [ 41 ]. In this most recent study conducted in Tianjin Medical University Cancer Institute and Hospital, China, decreased sRAGE and elevated AGE levels were found to increase breast cancer risk, thereby establishing negative concomitance of sRAGE and positive association of AGEs, respectively, with breast cancer.…”
Section: Diagnostic and Therapeutic Significance Of Targeting Ages An...mentioning
confidence: 99%